2010
DOI: 10.1093/mp/ssq010
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Cell Growth by Xyloglucan Oligosaccharides in Suspension-Cultured Tobacco Cells

Abstract: The incorporation of xyloglucan oligosaccharide (XXXG) into the walls of suspension-cultured tobacco cells accelerated cell expansion followed by cell division, changed cell shape from cylindrical to spherical, decreased cell size, and caused cell aggregation. Fluorescent XXXG added to the culture medium was found to be incorporated into the surface of the entire wall, where strong incorporation occurred not only on the surface, but also in the interface walls between cells during cell division. Cell expansion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…Changes in fresh weight and the higher and anticipated mitotic index peak with XGO treatment of tobacco BY-2 cells confirm previous reports [30,36] that XGOs stimulate cell division both as individual compounds and as the natural extract containing a mixture of XGOs used here. The fall in mitotic cell size in both control and XGO treated cells during the peak of mitotic index, regaining original size by the end of the culture period, is in line with previous observations in our lab [62].…”
Section: Xgos Stimulate Growthsupporting
confidence: 91%
See 3 more Smart Citations
“…Changes in fresh weight and the higher and anticipated mitotic index peak with XGO treatment of tobacco BY-2 cells confirm previous reports [30,36] that XGOs stimulate cell division both as individual compounds and as the natural extract containing a mixture of XGOs used here. The fall in mitotic cell size in both control and XGO treated cells during the peak of mitotic index, regaining original size by the end of the culture period, is in line with previous observations in our lab [62].…”
Section: Xgos Stimulate Growthsupporting
confidence: 91%
“…The null effect of XGO on cell size is also in agreement with the finding that XGO treatment of BY-2 cells shortens G1 whilst mitotic cell size remained constant [30]. Kaida et al [36] found a reduction in cell size associated with XGO treatment of a different tobacco cell culture system (XD-6 derived from N. tabacum L. var. Xanthi).…”
Section: Xgos Stimulate Growthsupporting
confidence: 83%
See 2 more Smart Citations
“…Most research in this field highlights their regulatory activity on cell growth and elongation, which relies in the molecular size, distribution, and levels of substituted xylosyl units with galactosyl and fucosyl residues [63]. It has been observed active xyloglucan oligomers (XGOs) accelerate cell elongation in peeled stem segments of Pisum sativum [64], and in suspension-cultured cells of Nicotiana tabacum, expansion led to cell division [65]. On the contrary, treatments with polymeric xyloglucan suppressed cell elongation [64][65], indicating that molecular size is a determinant factor of response specificity.…”
Section: Hemicellulose-derived Oligosaccharinsmentioning
confidence: 99%